Acoplamento de Sistemas de Fluxo a equipamento de espectrofotometria atómica e espectrometria de massa - aplicações em análise elementare em Química Clínica - Lopes, Cristina Manuela Pinto Vieira (2007)
In this dissertation several flow systems are described, which were developed in order to allow performing on line some sample pretreatments that are very common in laboratory analysis. These flow systems were intended to allow an easier application and expansion of the analytical potentialities of atomic spectrophotometry and mass spectrometry in elemental analysis, in Clinical Chemistry. In the Chapter of Introduction to this dissertation a brief description of the interest of the inorganic elemental analysis in Clinical Chemistry context is made, and flow strategies and the instrumental techniques more commonly used for that purpose are described, giving special emphasis to the description of the concepts and basic principles of ICP-MS technique. In the experimental work described in the first three Chapters, atomic spectrophotometric techniques were used and different flow strategies were employed, namely multicommutation and multipumping. Concretely, flow systems capable of adjusting, on line, the concentration of the analyte to the instrumental linear range, either by means of dilution procedures or by means of preconcentration procedures, were assembled. In the first work described involving multipumping, the results obtained in the study on the influence exerted by a pulsed flow, which is a feature of that type of systems, in the process of solutions aspiration and nebulization that are characteristic of atomic spectrophotometry equipment, are also presented. In the work presented in the last Chapter, a SIA flow system that allows the separation/preconcentration of the analytes, which in this case are PGEs, from urine samples, in order to allow their subsequent quantification by ICP-MS with quadrupole mass analyzer, is described.